2000
DOI: 10.1046/j.1525-1314.2000.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Tertiary fluid flow and pressure–temperature conditions in the Shimanto accretionary complex of south‐west Japan: constraints from fluid inclusions

Abstract: The pressure and temperature history of the Tertiary Shimanto belt of south‐west Japan has been elucidated by analysing fluids trapped in quartz crystals which grew syn‐kinematically along late‐stage brittle faults. The samples come from three areas that span the Paleogene exposures on the Muroto Peninsula of Shikoku Island. Applying microthermometric and laser Raman microsampling techniques to coeval water‐rich and carbonic fluid inclusions, we have constrained the pressure and temperature conditions that acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 10 publications
1
36
1
Order By: Relevance
“…Ultimately, some of this C is returned to shallower levels when it is released by devolatilization, to mix with fluid C generated by shallow-level biogenic and lower-T abiotic processes (and may again be precipitated in veins). It is worth noting that, despite the production of significant amounts of CH 4 in sediment-rich forearcs (Mashburn, 1985;Vrolijk, 1987;Lewis et al, 2000; this study), examination of the concentrations of reduced C (the organic C fraction) in high-P/T metasedimentary suites indicates very little effect of this loss to diagenetic and metamorphic fluids on whole-rock reduced C contents. Much of this C fraction is probably subducted to subarc depths and beyond into the deeper mantle (Bebout, 1995;Sadofsky and Bebout, 2003).…”
Section: Significance Of Observations In Paleo-accretionary Suites Inmentioning
confidence: 58%
See 2 more Smart Citations
“…Ultimately, some of this C is returned to shallower levels when it is released by devolatilization, to mix with fluid C generated by shallow-level biogenic and lower-T abiotic processes (and may again be precipitated in veins). It is worth noting that, despite the production of significant amounts of CH 4 in sediment-rich forearcs (Mashburn, 1985;Vrolijk, 1987;Lewis et al, 2000; this study), examination of the concentrations of reduced C (the organic C fraction) in high-P/T metasedimentary suites indicates very little effect of this loss to diagenetic and metamorphic fluids on whole-rock reduced C contents. Much of this C fraction is probably subducted to subarc depths and beyond into the deeper mantle (Bebout, 1995;Sadofsky and Bebout, 2003).…”
Section: Significance Of Observations In Paleo-accretionary Suites Inmentioning
confidence: 58%
“…A striking resemblance in structural character and lithology is observed between the low-grade parts (lawsonite-albite facies; Grove and Bebout, 1995) of the Catalina Schist and large parts of the Franciscan Complex and the Western Baja Terrane (Bailey et al, 1964;Ernst et al, 1970;Magaritz and Taylor, 1976;Sedlock, 1988aSedlock, , 1988bBebout and Barton, 1993;comparison with Sanbagawa Complex by Ernst et al, 1970; also see Lewis et al, 2000). However, veining and fluid-rock interaction and chemical/isotopic composition have not previously been studied in sufficient detail in most of the other areas to make direct comparisons with the Catalina results.…”
Section: Comparison With Other Studies Of Fluids In Paleo-accretionarmentioning
confidence: 97%
See 1 more Smart Citation
“…Other data also suggest a high paleogeothermal gradient in the forearc during the Paleogene. DiTullio et al (1993), Sakaguchi (1996) and Lewis et al (2000) suggested elevated Paleogene geothermal gradients in the Shimanto Belt in Shikoku, based on analyses of vitrinite reflectance, illite crystallinity and fluids trapped in quartz crystals.…”
Section: Thermo-tectonic Regime In the Forearc And Backarc Regionsmentioning
confidence: 99%
“…Several fluid inclusion studies have been conducted in the Shimanto Belt. The majority of these studies have focussed on the latest stage veins (Lewis et al . 2000) or several generations of “syn‐tectonic veins” (Sakaguchi 1996).…”
Section: Introductionmentioning
confidence: 99%